2002
DOI: 10.1063/1.1504882
|View full text |Cite
|
Sign up to set email alerts
|

Large g-factor enhancement in high-mobility InAs/AlSb quantum wells

Abstract: Articles you may be interested inThe effective g-factor in In0.53Ga0.47As/In0.52Al0. Transport and quantum electron mobility in the modulation Si δ-doped pseudomorphic GaAs/In 0.2 Ga 0.8 As/Al 0.2 Ga 0.8 As quantum well grown by metalorganic vapor phase epitaxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 19 publications
1
15
0
3
Order By: Relevance
“…At the lowest density p = 1.4×10 10 cm −2 , g p is as large as ∼ 28. Enhancement of g p with decreasing density has been observed in other material systems and can be attributed to an interaction effect [21,22]. We previously observed a quantum Hall ferromagnetic transition at p = 2.4 × 10 10 cm −2 and concluded that at this density the cyclotron gap equals the Zeeman gap [5].…”
mentioning
confidence: 99%
“…At the lowest density p = 1.4×10 10 cm −2 , g p is as large as ∼ 28. Enhancement of g p with decreasing density has been observed in other material systems and can be attributed to an interaction effect [21,22]. We previously observed a quantum Hall ferromagnetic transition at p = 2.4 × 10 10 cm −2 and concluded that at this density the cyclotron gap equals the Zeeman gap [5].…”
mentioning
confidence: 99%
“…They also note that despite the large g-factor enhancement in InAs QWs, the contribution of Zeeman spliting is much smaller than the splitting caused by the Rashba mechanism at low magnetic fields. Prior work reveals g-factors as large as À60 [11] for these materials at high magnetic fields. We Fig.…”
Section: Discussionmentioning
confidence: 99%
“…c [16]). Поверх бу-ферного слоя выращивалась 10-периодная " сглажи-вающая" сверхрешетка AlSb (2.5 нм)/GaSb (2.5 нм) при 480…”
Section: экспериментunclassified
“…таблицу). Ис-пользовались технологические приемы, обеспечивающие формирование на гетерограницах GaSb/InAs и AlSb/InAs связей In−Sb [14,16].…”
Section: экспериментunclassified